Writing performative Shakespeares new forms for performance criticism - Conkie, Rob (Cambridge University Press, 2016)
This innovative study offers a genuinely groundbreaking approach to Shakespeare in performance. Six chapters work like case studies, each highly creative in terms of visual form and structure – including puzzles, comics and pinboards – inviting the reader into playful engagement with the performative dimensions of Shakespearean production. The case studies include discussion of training and rehearsal processes; the materiality of the performance event and its various embodiments; the intertextual citations through which productions make meaning; and, in response to all of this, the multiplicity and variety of audience perspectives and interpretations. Conkie's production choices range from original practices to politicised adaptations, small-scale workshops to multimedia spectacles, offering inventive analyses of what Shakespeare might mean, or can be made to mean, at particular times and in specific places, at the start of the twenty-first century